Courses and Researches in the field of history of women and history of Women’s Education at the faculty of Humanities, University of Pécs, Hungary - Kéri, Katalin (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This paper provides a brief overview how research on history of women and history of women’s education going on, and in what courses they appear in the subject areas. The article focuses on the undergraduate, post-graduate and doctoral studies which show the contents of the gender perspective. The study also covers the issue what major research work has been done and what works were made in the past decades, and takes also an outlook on the comparative approach. This approach would help to clarify through what channels which people and works history of women and history of women’s education arrived at the Hungarian discourse. In our opinion source-centered, problem-based, and multi-perspective approach of history of education or history of women’s education provides not only more knowledge about the history of women for student teachers but a wider horizon of understanding Hungarian and European history of our societies. Gender aspects in teacher training programs are essential part of the competence development of future teacher which prepare student for independent problem processing, critical thinking, synchronistic and multi-perspective approaches, and following equity aspects.